Effects of extract solution from magnesium alloys supplemented with different compositions of rare earth elements on in vitro epithelial and osteoblast progenitor cells - Nie, Sheng; Chen, Jiakai; Liu, Chen; Zhou, Chenhui; Zhao, Jikuang; Wang, Zhepei; Sun, Jie; Huang, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Magnesium alloys (Mg-alloys) have been widely researched in recent years to serve clinically as a promising bioactive material. Supplementation with rare earth elements (REEs) has been of particular interest. In addition to their significant contributions to the mechanical properties of Mg-alloys, certain REEs have also been hypothesized to be able to positively participate in biological processes. Investigating the physiological benefits of Mg-alloys supplemented with REEs will facilitate their transition from theoretical to practical conversion. There are currently diverse results in terms of the cytotoxicity and biological effects of REEs. In this study, two culture systems were used: human umbilical vein endothelial cells and mouse osteoblastic progenitor cells. The effects of the extract solution from different compositions of Mg-alloys containing gadolinium (Gd), dysprosium (Dy), and yttrium (Y) were evaluated through observation of cell proliferation, viability, and specific cell functions. Within the range of weight percentages, these Mg-REE alloys did not show appreciable negative impacts on either cell line. Interestingly, moderate compositions (Mg-1.5Gd-1.5Dy-0.825Y-0.5Zr and Mg-2Gd-2Dy-1.1Y-0.5Zr) tended to enhance the osteoblastic activity and promote the vascularization process, providing insights into further explorations for optimizing compositions of REEs in novel Mg alloys.